Mr. Church [videorecording (DVD)] - Murphy, Eddie, 1961-; Robertson, Brittany; McElhone, Natascha, 1969- (Lionsgate, 2016)
A little girl and her dying mother obtain the services of a talented cook. What begins as a six-month arrangement spans fifteen years and creates a family bond that lasts forever.